United States Health Care Policymaking Ideological, Social and Cultural Differences and Major Influences - Ubokudom, Sunday E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Health care is a very important component of the American economy. The United States Centers for Medicare and Medicaid Services (CMS) put the 2008 direct health care expenditures at about $2.34 trillion, or about 16.2 percent of the nation$1 (Bs gross domestic product (GDP), or an average of $7,681 spent for every man, woman, and child in the country. Health care cost increases have caused very serious problems that threaten to bankrupt the system, providers, employers, and the families that pay the costs that their health insurance plans do not cover. Additionally, cost increases have reduced access to health care services, adversely aff ected the quality of care, and resulted in avoidable illnesses, premature deaths, and in health disparities based on race, ethnicity, and income. Consequently, health care reform has continuously been on the public and governmental agendas. It is out of this environment that several reform plans, including the 1993 Health Security Act, and the 2010 Patient Protection and Aff ordable Care Act (PPACA), were launched. Th is book examines the ideological, social, cultural, economic, and several other factors that dictate the various measures and approaches employed to tackle the perceived problems. The book has an index, tables, charts and fi gures, lists of major terms, and review questions for each chapter. Th is book will appeal to students in Master of Health Administration (MHA), Master of Public Health (MPH), Master of Public Administration (MPA), Master of Science in Nursing (MSN), health certificate programs, and junior and senior level undergraduate students in political science, public administration, public health, and public policy. In addition to serving as a core text for health policy and administration classes, the book will serve as a supplementary text for graduate level courses.s
Keywords: Economics; Public health; Economics/Management Science; Health Economics; Public Health; Political Science, general